STRATEGIES TO PREVENT REVERSE WATER GAS SHIFT REACTION VIA CU/ZNO NANOCATALYSTS WITH MFI-TYPE ZEOLITE SUPPORT - Megaria Napitupulu, Aditya
The commonly used commercial catalysts for the water gas shift (WGS) reaction are susceptible to sintering and are designed for standard conditions. Therefore, the development of suitable catalysts for processing the DRM gas product is crucial to minimize catalyst deactivation and enhance H2 production in a one-stage process known as the Medium Temperature Shift (MTS). This study aims to synthesize and characterize Cu/ZnO/ZSM-5 (CZZ) nanocatalysts for the WGS reaction. The catalysts were synthesized using the impregnation method, with a 5% mass loading of Cu and a Cu/Zn mass ratio of 1. This study focused on varying the SiO2/Al2O3 ratio to 30, 50, and 75, as well as varying the steam/CO ratios in the WGS reaction of 1 and 3–4. The catalysts were characterized using XRD, XRF, N2 physisorption, H2TPR, TGA, and SEM. The activity and stability tests were conducted in a fixed-bed reactor (300 °C, 1 atm, WHSV 12000 ml/gram-hour). Increasing the SiO2/Al2O3 ratio resulted in a decrease in catalyst activity for the WGS reaction. The CZZ catalyst with a SiO2/Al2O3 ratio of 30 (S/CO = 3–4) exhibited the best performance, with a CO conversion of 28,64% and an H2 yield of 40,38%, showing a good stability over a 32-hour test period. The commercial catalyst with a 58% mass loading of Cu achieved a CO conversion of 73,98%. However, when considering the mass of Cu, the 5% CZZ catalyst resulted in a 4,5 times higher CO conversion compared to the commercial catalyst. Under steam/CO = 1 conditions, the commercial catalyst only catalyzed the WGS reaction for 5,3 hours with lower CO conversion compared to the steam/CO = 3–4 conditions, whereas the CZZ catalyst achieved zero CO conversion throughout the reaction. The steam/CO ratio is the primary strategy for preventing the RWGS reaction. The equilibration of the active metal Cu mass fraction to 5% was carried out on the commercial catalyst and resulted the CO conversion of the CZZ catalyst (SiO2/Al2O3 = 30) was 9,3% higher than that of the commercial catalyst. TGA analysis was conducted on the spent catalysts and the CZZ (SiO2/Al2O3 30) showed the highest carbon deposition.